Analysis of students' perception of the use of information and communication technologies in the educational process through data science (Revista Electrónica Calidad en la Educación Superior, 2019)
This quantitative research analyzes the perceptions of students about the use of information and communication technologies in the educational context through data science. Data mining identifies predictive models about the impact of technology considering the aspects about the profile of students (age, gender and degree), digital tools Web 2.0 (Facebook, Twitter, Youtube videos) and Internet applications (web calculator, web simulator and cloud service). Likewise, linear regression indicates that the use of 2.0 tools and applications on the Internet positively influence the teaching-learning process. Finally, the science of data allows establishing predictive models on the use of technology in the educational field.
Keywords: Technology; higher education; data science; data mining; ICT